Biohydrogen Production from Palm Oil Mill Effluent by Locally Isolated Clostridium Butyricum Eb6 - Chong, Mei Ling (2009)
Hydrogen is a renewable, clean source of energy which has a great potential to be an alternative fuel. Abundant biomass from various industries could be a source for biohydrogen production where combination of waste treatment and energy production would be an advantage. Potential biomass that could be the substrates for biohydrogen generation include food and starch-based wastes, cellulosic materials, dairy wastes, palm oil mill effluent and glycerol. The objectives of this study were to isolate biohydrogen producing bacteria, to maximize the biohydrogen production in a synthetic medium and palm oil mill effluent (POME) and to improve the strain by overexpressing the hydrogenase gene in the host cell. A biohydrogen producer was successfully isolated from anaerobic POME sludge. The strain, designated as Clostridium butyricum EB6, efficiently produced biohydrogen during active cell growth. Controlled study was done on synthetic medium with 10 g/L glucose resulted in biohydrogen production at 948ml H2/L-medium and volumetric biohydrogen production rate of 172 mL H2/L-medium/h at initial pH 5.5. The supplementation of yeast extract at 4 g/L was found to have a significant effect with the highest biohydrogen production of 992 mL H2/L-medium. The effect of pH on biohydrogen production from POME was investigated, with the optimum biohydrogen production ability at pH 5.5. The maximum biohydrogen production and maximum volumetric biohydrogen production rate were at 3195 mL H2/L-medium and 1034 mL H2/L-medium/h, respectively. The biohydrogen content in the biogas produced was in the range of 60 - 70%. Optimization of biohydrogen production using synthetic medium was done on pH, glucose and iron concentration according to response surface methods (RSM) analysis. By central composite design (CCD) results, pH, glucose concentration and iron concentration were shown to significantly influence the biohydrogen gas production individually, interactively and quadratively (P<0.05) with some exception. The CCD results indicated that pH 5.6, 15.7 g/L glucose and 0.39 g/L FeSO4 was the optimum condition for biohydrogen production which gave a yield of biohydrogen at 2.2 mol H2/mol glucose. For the confirmation experiment model, t-test result showed that experimental data curve had a high confidence at 95% with t = 2.225. Based on the results of this study, optimization of the culture condition for C. butyricum EB6 significantly increased the biohydrogen production.Clostridium butyricum EB6 successfully produced hydrogen gas from POME. Central composite design and response surface methodology were applied to determine the optimum conditions for biohydrogen production (Pc) and maximum biohydrogen production rate (Rmax) from POME. Experimental results showed that the pH, temperature and chemical oxygen demand (COD) of POME affected both the biohydrogen production and production rate individually and interactively. The optimum conditions for biohydrogen production (Pc) was pH 5.69, temperature 36ºC and 92 g COD/L, with an estimated value of 306 mL H2/g carbohydrate. The optimum conditions for maximum biohydrogen production rate (Rmax) was pH 6.52, temperature 41ºC and 60 g COD/L, with an estimated value of 914 ml H2/ h. An overlay study was carried out to get an overall model optimization. The optimized conditions for the overall model was pH 6.05, temperature 36ºC and 94 g COD/L. [Fe]-hydrogenase (hydA) gene of C. butyricum EB6 was successfully amplified from the genomic DNA. Sequencing results of the hydA gene was identified with open reading frames of 1725 bp which encodes hydA of 574 amino acids with approximate size of 64 kDaltons. The hydA of C. butyricum was found 80.5% similar to hydA of C. acetobutylicum P262 and closely similar to Clostridia hydrogenase. A modified method of electroporation on C. butyricum EB6 was established for transformation of hydA. A hydA-expressing recombinant EB6 was successfully obtained with higher biohydrogen production from 4.2 L-H2/ L-medium to 4.8 L-H2/ L-medium compared to the wild type.